Analysis Of Taqiyuddin An-Nabhani's Thoughts On The Use Of Fiat Money And Its Impact On The Real Economy - Rianti, Mila; Izmuddin, Iiz; Alfin, Aidil; Rusyaida, Rusyaida (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
The development of the modern monetary system has undergone a major transformation, particularly with the adoption of fiat money as the primary medium of exchange. Fiat money, or paper money that is not backed by physical assets such as gold and silver, became the global standard after the collapse of the Bretton Woods system in 1971. Although this system offers flexibility in monetary policy, the use of fiat money also raises various economic problems, especially those related to inflation, exchange rate instability, and recurring financial crises. In An-Nabhani's view, the modern monetary system based on fiat money is part of an unfair global capitalist order that has the potential to cause economic instability, inflation, and inequality in the distribution of wealth. He emphasizes that only an Islamic monetary system based on the dinar (gold) and dirham (silver) can achieve economic justice and exchange rate stability. This study uses a qualitative approach with a library research method. The sources of analysis were obtained from several books, news articles, and scientific articles (accessible online through platforms and Google Scholar). In this context, it is important to have the ability to collect, document, and analyze findings relevant to the topic of this study. This study aims to analyze Taqiyuddin An-Nabhani's thoughts on the use of fiat money (paper money without the backing of real assets such as gold and silver) and its impact on the real economy. The results of the analysis show that fiat money opens the door to currency manipulation, excessive money creation (fiat money expansion), and speculation that is detrimental to the real sector, such as agriculture, trade, and industry. Conversely, according to An-Nabhani, a gold and silver-based monetary system will strengthen the real sector through exchange rate stability, encourage fair trade, and maintain people's purchasing power. This study recommends an evaluation of the fiat money system and opens up space for discussion on alternative sharia-based monetary systems in the era of the global economy.